Glucose-assisted polyol synthesis of silver nanoplates and nanoprisms in the presence of oxyethylated carboxylic acid - Alexander A. Titkov; Tatiana A. Borisenko; Olga A. Logutenko (Chimica Techno Acta)
This work reports a simple route to synthesizing silver nanoplates and nanoprisms through a polyol approach in the presence of oxyethylated carboxylic acid and glucose. The resulting particles were characterized by electron microscopy and X-ray diffraction (XRD). The introduction of glucose and NaOH into the system substantially increases the yield of nanoplates and reduces their thickness. The optimized reaction conditions can be used to produce, in a one-pot synthesis, silver nanoplates and nanoprisms which may have applications as metallic fillers in ink and paste formulations for 2D and 3D printing to fabricate functional components and devices.